Uji Aktivitas Antibakteri Infusa Kayu Secang (Caesalpinia Sappan L.) Terhadap Bakteri Escherichia coli ATCC 25922 dan Staphylococcus aureus ATCC 25923 - Leswara, Dianita Febrina; Nurhasanah, Devika; Retno P., Maysi (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2024)
Background: Escherichia coli and Staphylococcus aureus are two common types of bacteria that can cause infections in the human body. The treatment to overcome infections caused by Escherichia coli and Staphylococcus aureus bacteria is by administering antibiotics. The use of antibiotics that are not appropriate or not according to instructions can cause resistance so that alternative antibacterial agents from herbal plants begin to be developed. One of the plants known to contain antibacterial compounds is the secang plant. The secang wood stem is known to contain flavonoid and tannin antibacterial compounds. Objective: To determine the bacterial activity and Minimum Inhibitory Concentration (MIC) of secang wood infusa (Caesalpinia sappan L.) against Escherichia coli and Staphylococcus aureus. Method: Extraction of active compounds in secang wood was done by infundation method. The concentration of secang wood infusion that will be tested is 25%, 50%, 75% and 100%. Testing the antibacterial activity of secang wood infusion was carried out against Escherichia coli and Staphylococcus aureus using the well diffusion method. Results: Extraction of active compounds in secang wood is carried out using the infundation method. All concentrations of secang wood infusion tested 25%, 50%, 75% and 100%, showed antibacterial activity against Escherichia coli ATCC 25922 and Staphylococcus aureus ATCC 25923. The smallest concentration that showed inhibition of antibacterial activity was at a concentration of 25% with diameter of of inhibition zone is 20.52 mm in Escherichia coli ATCC 25922 and 20.58 mm in Staphylococcus aureus ATCC 25923 bacteria. Conclusion: Secang wood infusion has antibacterial activity with Minimum Inhibitory Concentration (MIC) at 25% concentration with strong inhibition